Analisis Penerapan Business Intelligence dan Knowledge Management dalam Strategi Retensi Pelanggan pada Platform Streaming Netflix Indonesia - Anggi Ismiyanti; Diana Puspita Sari; Nauroh Nazhiifah; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of digital technology has brought about significant transformations in the global entertainment industry, including in Indonesia. One manifestation of this change is evident in the presence of streaming platforms like Netflix, which have altered consumer consumption patterns for audio-visual content. This study aims to analyze how Netflix Indonesia utilizes Business Intelligence (BI) and Knowledge Management (KM) to maintain and increase customer loyalty. This research uses a qualitative descriptive method, collecting data from various scientific literature, industry reports, and relevant online sources. The results show that the implementation of BI enables Netflix to analyze user behavior, understand viewing preferences, and provide more personalized content recommendations. Meanwhile, KM plays a crucial role in internal knowledge management, content development, and service innovation. The synergy between BI and KM has been proven to support Netflix's strategy in improving user experience, retaining existing customers, and attracting new ones in the increasingly competitive Indonesian market.